Программная часть системы удаленного мониторинга и диспетчерского управления котельными автономных объектов теплоснабжения - Войтович, А. В. (ХНУРЕ, 2019)
This work is dedicated to the software development part of the boiler remote monitoring and dispatcher control system of autonomous central heating systems which gives the ability to monitor its basic technologic parameters over the Internet.